Executive functions, poverty and cognitive stimulation:a framework for future interventions - Bertella, María Adela (2018)
This paper presents the design and implementation of a executive functions’ stimulation program in a socially vulnerable population. The population was composed of 18 children between 6 and 11 years old, of both genders, who attend to Las Lilas Health Post (Pilar, Argentina), which were evaluated before and after the program’s implementation with the argentine adaptation of the Wechsler Intelligence Scale for Children WISC-IV. The stimulation was done through a specially made booklet to work the executive functions (working memory, cognitive flexibility, inhibition and planning). This pilot program allowed to build a nexus with the community, forming a institutional framework, on which new intervention programs are supported for the same population.